2015
DOI: 10.1038/bjc.2015.352
|View full text |Cite
|
Sign up to set email alerts
|

RANK/OPG ratio of expression in primary clear-cell renal cell carcinoma is associated with bone metastasis and prognosis in patients treated with anti-VEGFR-TKIs

Abstract: Background: Bone metastases (BMs) are associated with poor outcome in metastatic clear-cell renal carcinoma (m-ccRCC) treated with anti-vascular endothelial growth factor tyrosine kinase inhibitors (anti-VEGFR-TKIs). We aimed to investigate whether expression in the primary tumour of genes involved in the development of BM is associated with outcome in m-ccRCC patients treated with anti-VEGFR-TKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…These factors are the receptor activator of NF-kappa B (RANK), its ligand RANKL and the decoy receptor for RANKL, osteoprotegerin (OPG) [ 40 ]. Binding of RANKL to RANK triggers intricate and distinct signaling cascades to induce osteoclast development from haematopoietic progenitor cells as well as to activate mature osteoclasts [ 41 ]. Meanwhile, OPG negatively regulates RANKL binding to RANK and therefore inhibits bone turnover by osteoclasts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors are the receptor activator of NF-kappa B (RANK), its ligand RANKL and the decoy receptor for RANKL, osteoprotegerin (OPG) [ 40 ]. Binding of RANKL to RANK triggers intricate and distinct signaling cascades to induce osteoclast development from haematopoietic progenitor cells as well as to activate mature osteoclasts [ 41 ]. Meanwhile, OPG negatively regulates RANKL binding to RANK and therefore inhibits bone turnover by osteoclasts [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, OPG negatively regulates RANKL binding to RANK and therefore inhibits bone turnover by osteoclasts [ 42 ]. Several researches demonstrated that stimulation of RANK results in strong NF-kappa B activation and the NF-kappa B signaling pathway is relevant for RANKL-RANK-regulated osteoclast development and function [ 41 , 42 ]. These results indicate that ANGPLT4 might promote GCT progression by activating GCTSC proliferation and angiogenesis through the regulation of a series of downstream cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The relative levels of RANK/RANKL/OPG expression may influence prognosis in numerous cancer types including breast, lung, endometrial, renal cell and gastric cancers, osteosarcoma and multiple myeloma (Fig. 4a, b) [34][35][36][37][38][39][40][41]. In breast cancer, microarray analysis demonstrated that low RANK and high OPG expression were associated with longer OS (p = 0.0078 and p = 0.034, respectively) and disease-free survival (p = 0.059 and p = 0.040, respectively) [34].…”
Section: The Rank-rankl Axis In Cancer Biologymentioning
confidence: 99%
“…In another study, low RANKL expression has been associated with increased risk for bone metastases (p = 0.018) and shorter disease-free survival (p = 0.018) in breast cancer [40]. In metastatic clear cell renal cell carcinoma, an elevated RANK/OPG ratio has been associated with a shorter median time to metastasis (p = 0.014), progression-free survival (PFS) (p = 0.001) and OS (p = 0.0001) [35]. Moreover, RANK expression in clear cell renal cell carcinoma has been identified as an independent negative prognostic factor for both cancer-specific survival and recurrence-free survival (p < 0.001) [42].…”
Section: The Rank-rankl Axis In Cancer Biologymentioning
confidence: 99%
“…A study by Beuselinck [ 25 ] involving 129 RCC patients treated with anti-VEGFR-TKIs revealed that an elevated RANK/OPG ratio was associated with shorter time to bone metastasis, shorter median overall survival from initial diagnosis and shorter median progression-free survival. The results suggested that the RANK/OPG ratio in RCC might be associated with bone metastasis and prognosis in patients treated with anti-VEGFR-TKIs [ 25 ]. Nonetheless, further validation is warranted.…”
Section: Interactions Among the Immune System Bone And Tumormentioning
confidence: 99%